DINAMIKA KELAS MENENGAH, KESALEHAN, DAN PERAN GENDER DALAM PRODUK KALIGRAFI: STUDI KASUS INDUSTRI KALIGRAFI ERGO DI YOGYAKARTA - Lilik Maryanto (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2026)
This study analyzes the phenomenon of calligraphy consumption as a form of religious product among middle-class Muslim women, focusing on Ergo, a calligraphy industry based in Yogyakarta. Using Pierre Bourdieu’s theoretical framework—particularly the concepts of habitus, field, and various forms of capital (economic, cultural, and symbolic), along with distinction—this research seeks to understand how the aesthetic and religious consumption practices of calligraphy reflect the social, gendered, and class dynamics of contemporary urban Muslim society. The findings reveal that calligraphy functions not merely as a decorative element but also as a symbol of piety, social status, and religious identity within the family. Women play a dominant role in decision-making regarding the purchase, design, and arrangement of calligraphy in domestic spaces. Through their preference for minimalist and elegant designs, middle-class women convert economic capital into symbolic capital, reinforcing the family’s religious image and social respectability. In this process, a gendered habitus emerges—where the domestic sphere becomes a field in which women negotiate their agency and identity. However, this practice also displays a certain ambivalence. On one hand, women utilize domestic space to assert their agency and performativity of gender; on the other, they simultaneously reproduce patriarchal structures through subtle forms of symbolic violence, which naturalize women’s roles as guardians of home aesthetics and morality. Thus, the consumption of calligraphy among middle-class Muslim women can be understood as a social practice that intertwines religiosity, aesthetics, and social status—reflecting the complex interaction between religious habitus, symbolic capital, and practices of distinction within Indonesia’s Muslim middle-class culture.